Spatial variability of surface peat properties and carbon emissions in a tropical peatland oil palm monoculture during a dry season - Dhandapani, Selva; Girkin, Nicholas T.; Evers, Stephanie (Wiley, 2021)
The expansion of oil palm monocultures into globally important Southeast Asian tropical peatlands has caused severe environmental damage. Despite much of the current focus of environmental impacts being directed at industrial scale plantations, over half of oil palm land-use cover in Southeast Asia is from smallholder plantations. We differentiated a first generation smallholder oil palm monoculture into 8 different sampling zones, and further divided the 8 sampling zones into oil palm root influenced (Proximal) and reduced root influence (Distal) areas, to assess how peat properties regulate in situ carbon dioxide (CO2) and methane (CH4) fluxes. We found that all the physico-chemical properties and nutrient concentrations except sulphur varied significantly among heterogeneous zones. All physico-chemical properties except electrical conductivity, and all nutrient content except nitrogen and potassium varied significantly between Proximal and Distal areas. Mean CO2 fluxes (ranged between 382 and 1191 mg m-2 hr-1) varied significantly among heterogeneous zones, and between Proximal and Distal areas, with notably high emissions in Dead Wood and Path zones, and consistently higher emissions in Proximal areas compared Distal areas within almost all the zones. CH4 fluxes (ranged between -32 and 243 µg m-2 hr-1) did not significantly vary between Proximal and Distal areas, however significantly varied amongst heterogenous zones. CH4 flux were notably high in Canal Edge and Understorey Ferns zones, and negative in Dead Wood zone. The results demonstrate the high heterogeneity of peat properties within oil palm monoculture, strengthening the need for intensive sampling to characterise a land-use in the tropical peatlands.
Keywords: tropical peatlands; peat physico-chemical properties; peat nutrient content; oil palm plantation; methane